Ecological indicators for aquatic biodiversity, ecosystem functions, human activities and climate change - Jianjun Wang (Elsevier, 2021)
Inland aquatic ecosystems, such as streams, rivers, ponds and lakes, play an important role in maintaining global aquatic biodiversity and ecosystem services. They have been increasingly influenced by environmental change such as global warming, dam construction, habitat fragmentation, eutrophication and urbanization. However, our understanding of the impact of global change on aquatic biodiversity and ecosystem functions remains elusive. The aim of this special issue is to highlight the ecological indicators of aquatic biodiversity and ecosystem functions under global change. The special issue comprises 18 papers including both review and research articles. These papers cover a wide range of research topics, including testing ecological theory, environmental indicator development, biodiversity monitoring and bioassessment. By covering a broad taxonomic range from bacteria and phytoplankton to fish and spanning large spatial (much of Eurasia) and temporal scales (from one season to 25-years observations and 100-years paleo-reconstruction), these articles provide an overview of ecological phenomena from population and community perspectives. Several important implications emerged from these studies: (1) The studies of the long-term succession of biotic community provide important insights into the impacts of human activities and climatic changes on conservation and management of aquatic ecosystems; (2) Anthropogenic activities strongly affect aquatic biodiversity via modifying aquatic habitats and reducing habitat heterogeneity; (3) Biotic assemblages are valuable to for assessing the ecological status of freshwater ecosystems; (4) Aquatic ecosystems have unique characteristics different from other ecosystems, as the underlying drivers and assembly mechanisms of community structure in these ecosystems are highly distinct. Together, the selection of studies reinforces the importance of long-term monitoring, ecological indicator development, and applications of ecological theory in helping us to understand the response of aquatic biodiversity and ecosystem functioning to global change.